Exploring the Potential of Presean to Enhance Tourism in Sade Tourism Village, Lombok - Ferro Kusradi Anjar Caesar; Wanda Fitriana; I Wayan Kusuma Di Biagi; Ilham Hamid (Journal of Education and Social Science, 2025)
This research was written to identify various opportunities in utilizing the art of presean as the main attraction for tourists. The research method uses descriptive qualitative research. The data collection technique used in this research is descriptive method. The results of the study show that the art of presean has great potential in attracting tourists, especially in the village of Sade, which is a traditional village of the Lombok people considering that Lombok has nature that is still preserved and conservative. The results of this study reveal the lack of interest in tourism and the lack of interest of the local community in knowing the great potential in the art of presean as a form of economy in Lombok. The contribution of this research can be that an integrated planning of the sade village is carried out so that the growth and development of tourism activities there runs well as a whole in the entire tourist area of the sade village especially the presean event, as well as motivation in cultural interests especially young people and the planning of economic activities,, improving various service qualities that are considered poor by tourists and promotive and implementation efforts are improved.